The perceptions of and courase evaluation of the MPH degree by former Wits students who graduated in the period 2001-2007 - Mutloane, Thomas Albert Mothei (My University, 2008)
Background: In 1998 the Wits Faculty of Health Science began to offer a master’s programme in public health, through the School of Public Health, called the Master of Public Health. (MPH). The aim of the degree is to prepare “professionals to play leadership roles in the management, improvement and evaluation of health and the health care system” and to respond “to the needs of the people of South Africa and the African continent in their various living and working conditions”. Eight objectives have been set for the degree and these will be gone into in detail. Admission requirements to the programme are a bachelor’s degree of a minimum of four years duration in dentistry, medicine, nursing, occupational therapy, physiotherapy, etc. The programme can be offered on a full- or part-time basis. The following core modules are offered: Primary Health Care & Social Context of Health; Health Measurement I & II; Environmental & Occupational Health; Public Health Law & Health Systems Integration; Health Policy &Policy Analysis; Health Systems & Decentralization; Health Management Theory & Practice; Epidemiology; Health Care Financing etc. The primary motivation for this study was to determine the level of satisfaction of MPH graduates with the degree that they studied. Methods: The study was a cross-sectional study design. It was a survey that entailed using a pretested interview schedule or questionnaire. The study population was all MPH graduates up until June 2007 (N = 80). The participants were contacted telephonically or by e-mail by the researcher. The initial idea was to interview the participants telephonically, but most preferred to have the prepared interview schedule e-mailed to them. A Pilot Study (using 8 students) was conducted before commencement of the actual study. The pilot study revealed that the study questionnaire, although long and cumbersome, was do-able. A sample of 70 graduates was used and of these, 60 responded i.e. response rate of 86%. The researcher e-mailed the interview schedule and the information sheet which explained what the study was about and also made it clear that even if they had initially agreed to participate, they could still opt out if they later changed their minds. The information sheet further explained that their participation would be kept strictly anonymous, only codes would be used. The data gathering sheet (questionnaire) is in two parts: Part One is the “Course Evaluation” and Part Two is the “Value of the Masters in Public Health to Your Career”. Under Part One the candidates gave their views on the following: the content of various courses or modules offered; the teaching methods applied by the School; academic quality; administrative support; and research report support. Questions in each of these subsections were such that a rating on a scale of 1 to 5 (5 being excellent and 1 poor) had to be given and next to the score (rating) the candidate could also give a comment to explain the rating or how they felt about what was asked. At the end of each of the subsections are a number of open-ended questions that gave the candidate more scope for further written or verbal input. Similarly, Part Two has a rating on a scale of 1 to 5 (5 being extremely valuable and 1 less valuable) in terms of the value the particular course or module mentioned in the career of the graduate. There is also a “comment” portion accompanying every question. And at the end of this part are six open-ended questions aimed at eliciting more qualitative information based on the experiences of graduates post graduation and specifically focusing on the working environment. One very important question in this section is: “Would you or have you recommended this masters programme to others”. There are only two possible answers to this question: “Yes” – which signifies satisfaction with the programme, and “No” – which signifies unhappiness with the programme. It is a very important question in gauging client satisfaction. Results: On a rating of 1 to 5 (1 being poor whilst 5 is excellent the top rated modules were rated as follows under course evaluation: (i) Primary Health Care & Social Context of Health: All respondents (60 i.e. 100%) rated this module and gave it a rating of 4.13 (83%) (ii) Health Policy and Policy Analysis: Although 40 (67%) out of 60 people responded to this question, they gave it a rating of 4.25 (85%) (iii) Project Management for Public Health Practitioners: It was given a 4.27 (85%) rating by 44 (73%) out of 60 participants. (iv) Management in Health and Health Services: This module was given a rating of 3.83 (77%) by 58 (97%) out of 60 participants and (v) Introduction to Management in Theory and Practice: It was rated at 3.82 (76%) by 32 (53%) of the 60 participants. The same top-rated above modules were rated as follows under “Value of the Masters in Public Health (MPH) to your career” i.e. Part II of the questionnaire. (i)Primary Health Care & Social Context of Health: 3.26 (65%) as rated by 46 (77%) out 60 participants. (ii) Health Policy and Policy Analysis: 3.96 (79%) by 46 (77%) respondents out of 60. (iii) Project Management for Public Health Practitioners: 3.26 (65%) as rated by 46 (77%) out 60 participants. (iv) Management in Health and Health Services: 3.96 (79%) by 54 (90%) out of 60 participants. Discussion: Various laudable written comments made by participants about each module have been captured and recorded. These will be seen later. (i) Primary Health Care & Social Context of Health: This module received a very high from all the participants of the research study. The concepts of Primary Health Care and Social Context of Health have clearly been taught and grasped. (ii) Health Policy and Policy Analysis: This was the track that most graduates followed. It helped graduates understand and be able to analyse various policy issues in their respective organizations. Emphasis has not only been laid on policy formulation but also on policy implementation. (iii) Project Management for Public Health Practitioners: This module scored a very high rating under course evaluation. There is a perception that some public health services could be run as projects in an endeavour to increase efficiency. (iv) Management in Health and Health Services: A number of the students who come from the public health sector to do MPH are in management positions already, although they may not have a formal management qualification. Those who are not in management positions are preparing themselves to go into management positions in future. This module is of great assistance in preparing them for careers in management. The study has revealed that 98% of participants have stated that they would or have recommended the Wits MPH to others. And 80% of the participants have also stated that there has been a positive change in their careers since acquiring the MPH qualification.
Keywords: MPH evaluation; Master of Public Health degree; Unversity of the Witwatersrand, Faculty of Health Sciences